Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/03014460.2011.620625
|View full text |Cite
|
Sign up to set email alerts
|

BMI z-score is the optimal measure of annual adiposity change in elementary school children

Abstract: The BMI z-score is the optimal measure of annual adiposity change for elementary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 8 publications
0
53
0
Order By: Relevance
“…There were studies suggested BMI-Z to be a more reliable parameter [19], which was calculated according to the median and the standard deviation of age-and sex-specific reference values. Besides, with consideration of the effect of the normal growth and development of children and adolescents, BMI-Z score could better monitor the body fat percentage of the school-age children [20]. The intervention school had significant (P < 0.05) changes between baseline and postintervention values for BMI-Z and there was a nonsignificant trend for a decline for BMI-P.…”
Section: Discussionmentioning
confidence: 98%
“…There were studies suggested BMI-Z to be a more reliable parameter [19], which was calculated according to the median and the standard deviation of age-and sex-specific reference values. Besides, with consideration of the effect of the normal growth and development of children and adolescents, BMI-Z score could better monitor the body fat percentage of the school-age children [20]. The intervention school had significant (P < 0.05) changes between baseline and postintervention values for BMI-Z and there was a nonsignificant trend for a decline for BMI-P.…”
Section: Discussionmentioning
confidence: 98%
“…When we directly compared how change in %FM, a measure of relative FM that is complementary to percentage lean mass, correlated with change in all 3 indicators at the same time, we found that change in %FM was most strongly associated with change in BMIZ, particularly among AGA and LGA infants. These findings suggest that, as with older children (40,41), prospective change in BMIZ is an ideal surrogate indicator for adiposity accrual during the first 5 mo of life.…”
Section: Associations Between Change In Derived Indicators and Adp-mementioning
confidence: 94%
“…There is ongoing discussion regarding the optimal measure of adiposity in larger studies of children and adolescents. Some authors claim that BMI-for-age z-score (BMIz) is the best measure as it adjusts for the age and gender of the child7 while others claim that BMI most aptly represents a child's adiposity 8 9. BMI and BMIz are merely estimates of body fatness as these indices do not differentiate between the types of tissue that contribute to body weight (fat, muscle or bone mass).…”
Section: Introductionmentioning
confidence: 99%